A Bootstrapping Method for Improving the Classification Performance of the P300 Speller. - Cristancho-Cuervo, J. H.; Delgado-Saa, J. F. (Revista Mexicana de Ingeniería Biomédica, 2020)
In this paper, we present a novel approach to training classifiers in a speller based on P300 potentials. The method, based on bootstrapping, is a known strategy for generating new samples, but it is rarely used in neurosciences. The study first demonstrates how the performance of the classification task (detecting P300 and Non-P300 classes) could be sub-optimal in the traditional approach. Then, a new method for taking new samples from the training data is proposed. Each classifier is re-trained using balanced sub-groups of individual P300 and non-P300 samples. Data were collected from 14 healthy subjects, using 16 electroencephalography channels. These were filtered in bandpass and decimated. Subsequently, four linear classifiers were trained using the traditional method followed by the proposed one, with 1000, 2000 and 3000 samples per class. Results indicate an improvement in the accuracy and discrimination capacity of discriminative classifiers with the proposed method, maintaining the same statistical properties between the training and test data. By contrast, for generative classifiers, there is no significant difference in the results. Therefore, the proposed method is highly recommended for training discriminative classifiers in spell-based P300 potentials.